Risk evaluation of impurities in topical excipients: The acetol case - Jente Boonen; Lieselotte Veryser; Lien Taevernier; Nathalie Roche; Kathelijne Peremans; Christian Burvenich; Bart De Spiegeleer (Elsevier, 2014)
Pharmaceutical excipients for topical use may contain impurities, which are often neglected from a toxicity qualification viewpoint. The possible impurities in the most frequently used topical excipients were evaluated in-silico for their toxicity hazard. Acetol, an impurity likely present in different topical pharmaceutical excipients such as propylene glycol and glycerol, was withheld for the evaluation of its health risk after dermal exposure.An ex-vivo in-vitro permeation study using human skin in a Franz Diffusion Cell set-up and GC as quantification methodology showed a significant skin penetration with an overall Kp value of 1.82Ã10â3Â cm/h. Using these data, limit specifications after application of a dermal pharmaceutical product were estimated. Based on the TTC approach of Cramer class I substances, i.e. 1800Â Âµg/(dayâperson), the toxicity-qualified specification limits of acetol in topical excipients were calculated to be 90Â Âµg/mL and 180Â Âµg/mL for propylene glycol and glycerol, respectively.It is concluded that setting specification limits for impurities within a quality-by-design approach requires a case-by-case evaluation as demonstrated here with acetol. Keywords: Acetol, Impurity, Excipients, Transdermal penetration, Specification limits